Advocacy and Legal Assistance for Child Victims of Sexual Violence - Nur Ilmi Putri Febriyanti; Elmiati Nurdin; Evi Selviani; Nur Annisa Putri; Erni Yoesry (International Journal of Business, Law, and Education, 2026)
Children as a vulnerable group require special protection, especially when they become victims of sexual violence. In practice, child victims often experience various obstacles in obtaining justice, including limited access to legal aid, psychological trauma, and suboptimal assistance during the criminal justice process. This study aims to analyze the forms of advocacy and legal assistance provided to child victims of sexual violence, the role of law enforcement agencies and child protection agencies in providing legal protection, and the obstacles encountered in its implementation. This study uses a normative legal research method with a legislative and conceptual approach. The results show that advocacy and legal assistance for child victims of sexual violence include legal assistance, protection of the victim's identity, psychological recovery, and fulfillment of the victim's rights during the judicial process. The role of institutions such as law enforcement officers, legal aid agencies, and child protection agencies is crucial in ensuring the comprehensive fulfillment of the rights of child victims.